A review of recent machine learning advances for forecasting harmful algal blooms and shellfish contamination - Cruz, Rafaela C. (2021)
Funding: This work was funded by the project “MATISSE: A machine learning-based forecasting system for shellfish safety” (DSAIPA/DS/0026/2019). The work was also supported by national funds through Fundação para a Ciência e a Tecnologia (FCT) with references CEECINST/00102/2018, UIDB/04516/2020 (NOVA LINCS), UIDB/00297/2020 (CMA), UIDB/50021/2020 (INESC-ID), and UID/Multi/04326/2020 (CCMAR).